Predictors of poor first trimester outcome in asymptomatic women : the value of embryonic heart rate , mid sac diameter / yolk sac ratio & mid sac diameter / crown rump length - Abdulkadhim, Suaad (AL-Kindy College Medical Journal, 2019)
Background:  Ultrasound provides a powerful tool for assessing early pregnancy and detecting pregnancy failure at first trimester and promoting rapid effective management. Several  criteria have been established  to predict  the pregnancy outcome particularly in symptomatic women .Aim: To evaluate  asymptomatic women at the first trimester of pregnancy , to assess the efficacy of certain ratios as mid sac diameter (MSD)  / yolk sac ratio & crown rump length (CRL)/mid sac diameter (as indicator  of early first trimester oligohydramnios)  in predicting poor 1st   trimester outcomeType of the study: A cross-sectional study.Patients & Methods:  A sixty three asymptomatic women were enrolled in this prospective study . Transvaginal sonography was performed for confirmation of pregnancy viability & exclusion of multiple pregnancies 6-8 weeks of gestation & follow up ultrasound repeated at the beginning of second trimester to confirm the continuation of pregnancy and  viability of fetus. Several parameters assessed and tested against each others as embryonic heart rate , the size and morphologic criteria of gestational sac , yolk sac and  the crown rump length Results: The women  were classified into two groups: group A are those with successful outcome at the first trimester and group B are those with poor outcome of the 1st trimester . Decrease embryonic heart rate below 100 beat per minute  and low mid sac diameter/ yolk sac size ratio of < 1.9 , were found to be significant predictors of poor outcome however mid sac diameter/crown rump length ratio was not found to  have a similar significance Conclusion: In addition to the classical parameters  assessed  by trans-vaginal ultrasound, other important parameters need to be routinely applied as the  embryonic heart rate that predict poor outcome when less than 100 bpm . In addition to the ratio of mid sac diameter to the yolk sac diameter which  , if less than 1.9 ,  may point to abnormal  first trimester fate.